Foot-and-mouth disease vaccines: progress and problems. (2nd June 2016) - Cao, Yimei; Lu, Zengjun; Liu, Zaixin
ABSTRACT: Foot-and-mouth disease (FMD) has been a major threat to livestock across the world. The predominant method of controlling this disease in endemic regions is through regular vaccination with inactivated vaccine. However, there are many limitations. For instance, cultivation of virulent FMD virus (FMDV) in the manufacturing units poses a risk of escape from production sites. Vaccines may sometimes contain traces of FMD viral non-structural proteins (NSPs), therefore, interfering with the NSP-based serological differentiation infected from vaccinated animals (DIVA). Moreover, vaccines are unable to eliminate virus from carrier animals. To address the shortcomings of inactivated vaccines, many efforts are currently devoted to develop novel vaccines including attenuated and/or marker inactivated vaccines, recombinant protein vaccines, synthetic peptide vaccines, and empty capsid vaccines. Here, we review the research progress of novel vaccines, problems that remain to be solved, and also raise some suggestions that would help in the development of FMD vaccines.